CIMMYT-CCAFS research prepares maize breeding programs for future climates - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
CIMMYT’s research has informed the agenda of maize breeding programs in sub-‐Saharan Africa, to ensure that new varieties developed will be tolerant to heat stress as well as drought. CIMMYT’s climate projections for maize-‐producing areas in sub-‐Saharan Africa highlighted the increasing prevalence of heat stress and identified hotspots of vulnerability. Researchers analysed commercially available maize varieties and new drought tolerant varieties developed under the Drought Tolerant Maize for Africa (DTMA) project, by phenotyping and modelling crops under expected future climates. The results highlighted the susceptibility of these varieties to increased heat stress. The research also identified potential yield gains that could be made through adapting the existing breeding pipeline to address the potential effects of future climates, particularly heat stress.